Mamma Mia, P‐glycoprotein binds again. Issue 23 (20th October 2020) - Callaghan, Richard; Gelissen, Ingrid C.; George, Anthony M.; Hartz, Anika M. S.
Abstract : The levels of amyloid peptides in the brain are regulated by a clearance pathway from neurons to the blood–brain barrier. The first step is thought to involve diffusion from the plasma membrane to the interstitium. However, amyloid peptides are hydrophobic and avidly intercalate within membranes. The ABC transporter P‐glycoprotein is implicated in the clearance of amyloid peptides across the blood–brain, but its role at neurons is undetermined. We here propose that P‐glycoprotein mediates 'exit' of amyloid peptides from neurons. Indeed, amyloid peptides have physicochemical similarities to substrates of P‐glycoprotein, but their larger size represents a conundrum. This review probes the plausibility of a mechanism for amyloid peptide transport by P‐glycoprotein exploiting evolving biochemical and structural models.